The Adaptation of Career Adaptability Scale on Vocational High School Students (Jurnal Bimbingan Konseling, 2020)
Career Adapt-Abilities Scale is the most frequently used scale to assess career adaptability that has been tested in various countries. Since there has been no adaptation of this scale in Indonesian version, therefore, this study aimed to adapt Career Adapt-Abilities Scale to Indonesian, and examine its validity as well as reliability. The adaptation processes covered (1) understanding original test behavioral indicators, (2) performing back translation, (3) readability test, (4) items discrimination test, (5) validity estimation, and (6) reliability test. The respondents of this study were 797 students coming from Vocational High School (SMK) throughout Temanggung Regency. After the processes were carried out, the study resulted the Indonesian version of Career Adapt-Abilities Scale that consisted of 24 items. Further, the results of confirmatory factor analysis found that all items in Indonesian version were valid, and gained the coefficient values of 0.77 to 0.85 in reliability test. At last, this Career Adapt-Abilities Scale is recommended to be applied as one of career guidance instruments in Vocational High School, and researches